The secret language of girls - Dowell, Frances O'Roark. (New York : Atheneum Books for Young Readers, 2004)
Marylin and Kate have been friends since nursery school, but when Marylin becomes a middle school cheerleader and Kate begins to develop other interests, their relationship is put to the test.
Sequel: The kind of friends we used to be.
Keywords: Best friends; Friendship; Schools